Change of the metabolomic profile during short-term mononuclear cell storage - Steininger, Philipp; Strasser, Erwin; Ziehe, Bettina; Eckstein, Reinhold; Rauh, Manfred (Vox Sanguinis, 2017)
BACKGROUND AND OBJECTIVES: Short-term storage of leukapheresis products used for immunotherapeutic mononuclear cell (MNC) products is a frequent event. The analysis of time-related metabolic patterns enables the characterization of storage-related effects in MNCs and the hypothesis-based optimization of the MNC medium. MATERIALS AND METHODS: The MNC products from seven leukapheresis procedures were stored within a closed bag system for 48 h. Concentrations of amino acids, biogenic amines, phospho- and sphingolipids and hexoses in the medium were measured by targeted metabolomics. The viability of MNC subpopulations was assayed by Annexin V (AnV) and JC-1 staining. RESULTS: Glucose depletion and a significant change of the acylcarnitine profile are early events within the first 24 h of storage. In contrast, for most amino acids, the maximum increase was observed at 48 h of storage as mirrored by an increase in the amino acid levels by a mean factor of 1·2 (1·3, 2·0) after 6 h (24 h, 48 h, respectively). This was except for the concentrations of glutamine and lysine, which did not change significantly. The taurine concentration showed a twofold increase within the first 24 h and remained constant thereafter. The steepest increase in AnV+and 7-AAD+CD4+T cells was found between 24 and 48 h. CONCLUSION: The time-course of apoptosis and metabolic patterns in the MNC products demonstrate that 24 h of storage is a decisive time-point, as afterwards key metabolic pathways showed nonlinear detrimental changes. Optimization of storage by supplementation of specific substrates demands therefore an early intervention.
EVALuna2:32783